Ethical issues in corporate governance principles: with reference to directorsʼ duties - Hassan, Halyani; Ibrahim, Ahmad (Eubios Ethics Institute, 2010)
Corporate governance is about how a company is being controlled and managed in the interests of its shareholders and stakeholders. Codes of corporate governance embody rules of conduct and best practices which are directed to the controller of the company i.e. the board of directors. Corporate governance principles have been introduced to enhance accountability and transparency in a company. In most circumstances these are reflected in the duties and responsibilities of the directors as stated in the relevant statutory provisions. On the other hand, ethical issues in business corporations relate with integrity, honesty and fairness. This paper intends to highlight and examine the ethical elements in those statutory provisions which have been legislated based on corporate governance principles. The study would be focused on directorsʼ fiduciary duty and duty of care. It would look beyond corporate social responsibility practices which have often been described as companyʼs ethical duty. It is perceived that those duties stated in the statutory provision had imposed ethical behavior upon the directors. Hence, the corporate governance principles which emphasis on accountability and transparency had actually been mooted from values such as integrity, honesty and fairness. The main terms of reference of this paper are corporate governance principles, directorsʼ duties and ethical issues. Research methodologies adopted are doctrinal and statutory analysis.